Fetal brain injury in survivors of twin pregnancies complicated by demise of one twin as assessed by in utero MR imaging. (18th March 2015) - Griffiths, P. D.; Sharrack, S.; Chan, K. L.; Bamfo, J.; Williams, F.; Kilby, M. D.
Abstract Objective The aim of this study was to quantify the risk of brain abnormalities in single‐twin demise of monochorionic pregnancies and to describe the type of brain injuries using ultrasound and in utero magnetic resonance (iuMR) imaging. Methods Monochorionic twin pregnancies complicated by the demise of one twin referred between 2004 and 2013 were reviewed. Ultrasound was performed in a tertiary centre prior to iuMR. The cases were subdivided into those associated with co‐twin loss following fetoscopic laser ablative treatment for twin–twin transfusion syndrome (TTTS) and those associated with spontaneous fetal demise. Results Sixty‐eight cases were identified, 27/68 following treatment for TTTS and 41/68 with spontaneous fetal demise. Nine (13.2%) had brain abnormalities on iuMR, and the rate of brain abnormalities was similar in the two groups. Expert ultrasound and iuMR findings agreed in three out of nine of those cases, and in six out of nine cases, ultrasound underestimated or missed the pathology. Conclusion Monochorionic twin pregnancies with single fetal demise are complex pregnancies with increased risk of acquired brain pathology, although the rate of brain abnormalities in our study is lower than that of other publications. iuMR in such complicated pregnancies is a useful adjuvant imaging technique that appears to detect brain pathologies better than prenatal ultrasonography. © 2015 John Wiley & Sons, Ltd.